2003
DOI: 10.1002/bit.10548
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed addition of limiting‐carbon during Aspergillus oryzae fermentation leads to improved productivity of a recombinant enzyme

Abstract: Fungal morphology in many filamentous fungal fermentations leads to high broth viscosity which limits oxygen mass transfer, and often results in reduced productivity. The objective in this study was to determine if a simple, fed-batch, process strategy-pulsed addition of limiting-carbon source-could be used to reduce fungal broth viscosity, and increase productivity of an industrially relevant recombinant enzyme (glucoamylase). As a control, three Aspergillus oryzae fed-batch fermentations were carried out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 53 publications
4
24
0
Order By: Relevance
“…However, the morphological behavior observed during the studied industrial cultivation of S.clavuligerus is similar to that observed by Pons et al [28] in Streptomyces ambofaciens with a complex medium: a fragmentation and a decrease of HGU were observed at the onset of the production of spiramycin. Similar findings have been described by Li et al for A. oryzae [29]. These phenomena might be general and should be investigated in more detail.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…However, the morphological behavior observed during the studied industrial cultivation of S.clavuligerus is similar to that observed by Pons et al [28] in Streptomyces ambofaciens with a complex medium: a fragmentation and a decrease of HGU were observed at the onset of the production of spiramycin. Similar findings have been described by Li et al for A. oryzae [29]. These phenomena might be general and should be investigated in more detail.…”
Section: Resultssupporting
confidence: 66%
“…By the use of image analysis, this work gives a quantitative description of how changes on two of the most influential industrial process parameters namely, inoculum age and scale change, can affect the morphology and apparent viability of S.clavuligerus and consequently the productivity of fed-batch fermentations. It can be used to investigate the effect of other operation conditions likely to affect the productivity at industrial scale such as mixing time and pulse-feeding [29].…”
Section: Resultsmentioning
confidence: 99%
“…All fermentations ran in fed-batch mode. Precise details cannot be given for commercial reasons, but approximately similar processes have been reported previously (Amanullah et al, 1999(Amanullah et al, , 2002Bhargava et al, 2003aBhargava et al, ,b, 2005Li et al, 2002a,b). The pilot work was focused on fine tuning of the process prior to up-scaling.…”
Section: Methodssupporting
confidence: 56%
“…It was shown that with a small increase in the RMSECV of the apparent viscosity the batch time can be ignored which indicates that the PLS model uses the physical information from the biomass size distribution in a meaningful way. Further, the factor of feed mode (pulsepause vs. continuous mode), known to influence morphology and viscosity (Bhargava et al, 2003a(Bhargava et al, ,b, 2005, improves the predictive power of the model of t y , K, and m app indicating that the model is sensitive to the concept of the ''morphology-viscosity'' type of a strain. Analysis of the resulting regression model can be used to increase understanding of the correlations between the size of the particles and the rheological parameters.…”
Section: Discussionmentioning
confidence: 94%
“…Bhargava et al (2003) reported improved volumetric production of glucoamylase by Aspergillus niger when the substrate maltodextrin was fed for 90 seconds every five minutes. This was because more feed was added as soon as more dissolved oxygen was available.…”
Section: Effects Of Substrate Fluctuations In Microbial Cultivationsmentioning
confidence: 99%